Food Identity and its Impact Upon the Study Abroad Experience - Ciliotta-Rubery, Andrea (Journal of International Students, 2016)
Study Abroad programs go to great lengths to prepare students for living and working in environments unlike their own. While much of the preparation focuses on the challenges of university life, travel, safety and the like, this paper suggests that an early and thoughtful discussion of “food identity” will provide students with the tools necessary to become more insightful of the culture of their host country. Since eating is vital, regional foods provide a wonderful opportunity for entering into the culture of another. By exposing students to such factors as the malleable, political, gendered and deliberately constructed nature of food identities, students become more cognizant of the complex histories of other people and places, through the portal of their food.